Penerapan Teorema Bayes untuk Mendiagnosa Penyakit Telinga Hidung Tenggorokan (THT) - Imamah Imamah; Akhmad Siddiqi (Universitas Bumigora, 2019)
Ear, Nose and Throat Disease (ENT) is a common disease that is often considered a harmless disease by people, so they assume there is no need to see a doctor. But in fact, ENT disease can also provide serious disorders if not treated early and right, so the expert system of ENT is needed for early detection before the patient decided to see a doctor or not. Based on these problems, this study proposed the application of the Bayes theorem for early detection of ENT disease. The types of diseases used in this study were six types and had 22 symptoms. User inputs the symptoms of a disease, then the system will provide a diagnosis. This diagnosis can be used as an initial reference for sufferers and can be used as a reference for young doctors who are taking medical education with an ENT specialist. In this initial research, testing was carried out to calculate the computational time needed by the system to diagnose ENT disease. Based on this research, we found that the average computing time needed by the system to diagnose is 00:09:54 or Nine minutes, fifty-four seconds.